2012
DOI: 10.2478/v10153-011-0082-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic aspects in schizophrenia etiology and pathogenesis

Abstract: Epidemiological evidence suggests that etiology of schizophrenia may involve both the influence of genetic factors specific for the individual and the impact of the environment. It is quite likely that a crucial role in the disease development is played by molecular mechanisms mediating the interaction between genes and environment. Modern research have shown that epigenetic mechanisms or chemical modifications of deoxyribonucleic acids (DNA) and histone proteins remain unstable throughout life and can be chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The covalent binding of a methyl group to the 5′ end of cytosine in DNA CpG dinucleotides can silence the gene and inhibit gene expression [7]. It has been proposed that measuring DNA methylation changes may provide a better measure of environmental impacts than evaluating environmental factors themselves [8, 9]. Due to their dependence on genetic and environmental factors, epigenetic markers integrate information from both causal contributors to phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent binding of a methyl group to the 5′ end of cytosine in DNA CpG dinucleotides can silence the gene and inhibit gene expression [7]. It has been proposed that measuring DNA methylation changes may provide a better measure of environmental impacts than evaluating environmental factors themselves [8, 9]. Due to their dependence on genetic and environmental factors, epigenetic markers integrate information from both causal contributors to phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence suggests that the etiology of schizophrenia may involve both the influence of genetic factors specific to the individual and the impact of the environment. It is quite likely that a crucial role in disease development is played by molecular mechanisms mediating the interaction between genes and the environment [Popov et al 2012]. Until recently, little was known about the role of vitamin D in brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Abu-Elneel et al identified 28 miRNAs (out of 466 miRNAs examined) that were differentially expressed between autism and control in a postmortem brain analysis [256]. The differential expression of miRNAs in autistic individuals was also examined in whole blood and lymphoblastoid cell samples [257,258].…”
Section: Micrornasmentioning
confidence: 99%